Knowledge Sharing Instruktur Milenial di Balai Latihan Kerja Medan, Kota Bekasi dan Kota Sorong - Rao, Don Gusti; Hasyim, Mochamad Sarif (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The advancement of technology and the digital competency dynamics of Generation Z have rendered the role of instructors in the Knowledge Sharing (KS) process at Vocational Training Centers (BLK) increasingly vital. Given that the majority of trainees are members of Generation Z, while the instructors largely belong to the millennial generation (Generation Y), an adaptive attitude from instructors during the KS process in class becomes essential. The intended outcome of the learning process at BLK is to ensure that students understand and are able to implement practical materials, thereby maximizing their application in the workplace. This study aims to explore the KS process conducted by millennial instructors at BLKs in three designated zones: Medan in the western zone, Bekasi City in the central zone, and Sorong City in the eastern zone. The selection of BLKs in each city was determined using purposive sampling, resulting in randomly selected training centers. A qualitative approach was employed, including direct observation in the western and central zones and interviews with a total of 15 informants—five from each zone—comprising one Generation X instructor, two millennial (Generation Y) instructors, and two Generation Z students. Data were analyzed using source triangulation by validating interview transcripts to obtain comprehensive and accurate information. The findings reveal that the effective use of technology, flexibility in teaching methods, engaging and interactive tools, and an open attitude towards questions and criticism are key factors contributing to an optimal KS process. It is expected that the results of this study can serve as constructive recommendations for the respective BLKs.